2011
DOI: 10.1093/annhyg/mer082
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microorganisms, Endotoxin, and Dust Concentration in Wood Factories in Italy

Abstract: Exposure to biological agents and dusts occurs in homes and occupational environments and it is known to cause adverse health effects. There is limited information concerning the occupational exposure levels of airborne biohazard during wood processing, but this exposure is associated with a range of adverse health effects. Control of exposure to microbiological hazards and dust in woodworking is not easy. In fact, various types of wood are commonly used and they generate complex mixtures of dusts and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
11
0
3
Order By: Relevance
“…The bacterial and fungal concentrations in his study were 3,471 and 11,140 CFU/m 3 , respectively. The bacterial concentration reported by Gioffrè et al [ 9 ] was 130-2,000 CFU/m 3 , and the predominant fungal species were A. niger, A. flavus , and Penicillium spp., in accordance with our results. In the study of Prażmo et al [ 12 ], the dominant bacteria were Enterobacteriaceae and Rahnella spp.…”
Section: Discussionmentioning
confidence: 97%
“…The bacterial and fungal concentrations in his study were 3,471 and 11,140 CFU/m 3 , respectively. The bacterial concentration reported by Gioffrè et al [ 9 ] was 130-2,000 CFU/m 3 , and the predominant fungal species were A. niger, A. flavus , and Penicillium spp., in accordance with our results. In the study of Prażmo et al [ 12 ], the dominant bacteria were Enterobacteriaceae and Rahnella spp.…”
Section: Discussionmentioning
confidence: 97%
“…Se reconoce que la presencia de polvos de madera en el aire del interior es un factor de riesgo laboral que afecta negativamente la salud humana debido a la composición química de dichos polvos, así como por ser un medio de transporte para bacterias y hongos (Gioffre et al 2012). Internacionalmente se reconoce que los polvos de madera provocan enfermedades respiratorias alérgicas y no alérgicas, como son: asma no alérgica, rinitis, bronquitis crónica, obstrucción crónica, alveolitis alérgica extrínseca y cáncer, entre otras (Kenny et al 1999, Schlünssen et al 2001, Douwes et al 2003, Ideara 2014.…”
Section: Discussionunclassified
“…Los polvos se estabilizaron por 48 h en horno eléctrico, a una temperatura de 26 ºC y se pesaron en una balanza analítica de cuatro decimales (Ohaus Adventurer). Una vez realizado el muestreo, los filtros se estabilizaron y se pesaron bajo las mismas condiciones (Gioffre et al 2012). La concentración de polvos de madera en el filtro fue obtenida usando las fórmulas 1 y 2 (Airmetrics 2012).…”
Section: Análisis Gravimétricounclassified
See 1 more Smart Citation
“…Although bacteria and bacterially derived endotoxins have been a dominant hygiene concern in this industry, a number of investigators have shown that fungal contamination also contributes to respiratory symptoms, lung function impairment and airway hyperresponsiveness among wood processing workers [1, 13, 18, 2023]. Despite the potentially important role of fungal contamination of wood dust, however, the presence of fungal spores in the sputum of exposed wood workers has not been assessed, either as a measure of exposure or as a potential correlate of adverse effects of this working environment.…”
Section: Introductionmentioning
confidence: 99%